THE EFFECTIVENESS OF INTERPRETATION RELATED TO ENVIRONMENTAL CLEANLINESS AND WATER IN THE EFFORTS TO CONTROL ITEMS IN BELAWAN SICANANG - Yustika, Dilla; Amalia Putri, Dea; Safitri, Dedek; Fernanda, Deza; Permata Sari, Dian; Himayanti Nasution, Diana; Kamala Sari, Ayu; Nuriyah, Nuriyah; Silvia Sabillah, Vany; Hasibuan, Rapotan (LPPM Univ. Ibn Khaldun Bogor, 2022)
Skin that is not maintained healthy can cause various types of skin diseases. Manalu (2019) states that there is a relationship between the use of river water and the incidence of dermatitis symptoms. Based on a preliminary study conducted by the people of Bromo Island, Mantuil Village, the main water sources are river water and PDAM water. The Belawan Sicanang area has attracted quite a bit of attention because of the poor environmental conditions and water conditions that trigger itching. Therefore Team 11 PBL FKM UINSU is interested in conducting environmental surveys and interventions to help the community around Belawan Sicanang. Methods: The design of this research is descriptive quantitative, which is to see the percentage of the community picture related to how the team's intervention works. The population used is the Sicanang community and the sample in the study was taken by purposive sampling as many as 74 respondents. Result: Most people understand and accept the PBL Team intervention very well. 97.2% of the community understood the content of the material presented by the team, 88.3% of the community considered that the team was very well aware of the materials and interventions carried out, and 84.3% of the community liked the intervention carried out by the team because the equipment was easy to obtain so that they can implement it.